Determination Of Prognostic Markers For Cervical Cancer - Ahmad, Rahmatul Wahida (2008)
Biomolecular factors could possibly improve the prediction of prognosis and diagnosis in cancer. Understanding specific molecular pathways could possibly shed some light in improving therapeutic modalities so that the treatment plan can be modified to suit individual cases. Various markers including factor VIII related antigen (MVD), Cyclooxygenase-2 (COX-2), E-cadherin, human telomerase reverse transcriptase (hTERT) and insulin like growth factor receptor (IGF-R) have been shown to play important roles in carcinogenesis and in predicting the prognosis of cervical cancer. Proliferation of tumor cells is uncontrolled, excessive and requires less growth factor since tumor cells have aberrant expression of IGFR.